Research on the Influencing Factors of College Students’ Exercise Behavior in Zhengzhou Sias University - Zhang, Longfei; Hengsuko, Eksask; Eakronnarongchai, Wiradee; Promthep, Kreeta (Journal of Neonatal Surgery, 2025)
also have a miderate impact on the physical exercise behavior of college students in Zhengzhou Sias College. The purpose of this study was to investigate the influencing factors of college students' physical exercise behavior in Zhengzhou Sias University, express the correlation of each influencing factor, and put forward corresponding suggestions on this basis. Combined with the health ecology model, the main dimensions of the impact survey were determined through the literature method and expert interview method, and the questionnaire on the influencing factors of physical exercise behavior of college students in Zhengzhou Sias University was designed. The design includes 7 first-level indicators, namely subjective awareness (F1), school site facilities (F2), school sports policy (F3), personal diet and rest (F4), interpersonal relationship support(F5), internet influence (F6), and personal health tendency (F7). The research results showed that school sports policy (F3), personal diet and rest (F4), and interpersonal relationship support (F5) have the strongest impact on college students’ exercise; school site facilities (F2) and personal health tendency (F7) have moderate impact, whereas F1 subjective awareness (F1) and internet influence (F6) have no impact on college students’ exercise. Therefore, sports policy, personal diet and rest, and interpersonal relationship support are the most important factors affecting the physical exercise behavior of college students in Zhengzhou Sias College, and the school facilities and students' personal health tendency